The Impact ef The Covid-19 Pandemic on Food Security of Farmers' Households in Pringgasela District, East Lombok Regency - aditya tama, bayu; Sahidu, Arifuddin; Nurjannah, Siti (Yayasan Siti Widhatul Faeha, 2025)
The COVID-19 pandemic has significantly impacted food security and the biological vulnerability of farming households, especially in rural areas heavily dependent on agriculture. This study aims to analyze the effects of the COVID-19 pandemic on the food security of farming households in Pringgasela District, East Lombok, and its relation to the biological vulnerability of farmer families. A descriptive quantitative and qualitative method was used, with data collection techniques including interviews, questionnaires, and documentation. The study sample consisted of 30 farming households directly affected by the pandemic. The results show that the pandemic disrupted food availability (73.33% of respondents) and access to food (86.67% of respondents) due to social restrictions and distribution disruptions. The majority of respondents (90%) reported food shortages and difficulties in meeting nutritional needs. Socio-economic factors such as low income, low education, and dependence on small-scale farming exacerbated vulnerability to malnutrition and health issues. Major challenges included decreased food production, limited access to quality food, and food price instability. These findings highlight the importance of interventions in the form of social and economic support to improve food security and enhance the quality of life for farming households during a crisis.